2022
DOI: 10.1115/1.4053855
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of a Mixed Flow Turbine Using 3D Blading

Abstract: Mixed flow turbines have reached a level of maturity where iterative performance improvements are small, with real performance benefits coming from better matching to a given application as opposed to improvements in technology. One design feature of mixed flow turbines used to control rotor stress is the radial fibre constraint, wherein blade material is stacked radially outward along the blade. While this constraint yields a mechanical benefit, it constrains the aerodynamic design significantly, with the bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The result of geometric transformations is obtaining a high-quality digital model of Mixed Flow turbines in the SolidWorks CAD system [25]. Thus, it can be concluded that the geometry of Mixed Flow turbines is a complex and complex task, and, accordingly, the creation of digital models of such a product requires the involvement of significant scientific potential and highly qualified technical personnel capable of, on the one hand, performing the role of system integrators and implementers of lean production tasks within Lean-Green practices, and on the other hand, to be able to solve related problems of mechanical engineering technology from the idea to the production of a product using digital services [28,29]. Elliot M. et al [30] noted that, according to modern knowledge about Mixed Flow turbines, the natural advantages of the performance of such turbines are related to better compliance with the given geometric characteristics and not, for example, to improvements in their manufacturing technology.…”
Section: Figure 3: Mixed Flow Turbine Blade Profilementioning
confidence: 99%
“…The result of geometric transformations is obtaining a high-quality digital model of Mixed Flow turbines in the SolidWorks CAD system [25]. Thus, it can be concluded that the geometry of Mixed Flow turbines is a complex and complex task, and, accordingly, the creation of digital models of such a product requires the involvement of significant scientific potential and highly qualified technical personnel capable of, on the one hand, performing the role of system integrators and implementers of lean production tasks within Lean-Green practices, and on the other hand, to be able to solve related problems of mechanical engineering technology from the idea to the production of a product using digital services [28,29]. Elliot M. et al [30] noted that, according to modern knowledge about Mixed Flow turbines, the natural advantages of the performance of such turbines are related to better compliance with the given geometric characteristics and not, for example, to improvements in their manufacturing technology.…”
Section: Figure 3: Mixed Flow Turbine Blade Profilementioning
confidence: 99%